A novel mHealth application for improving HIV and Hepatitis C knowledge in individuals with opioid use disorder: A pilot study. (1st September 2018) - Ochalek, Taylor A.; Heil, Sarah H.; Higgins, Stephen T.; Badger, Gary J.; Sigmon, Stacey C.
Highlights: This sample of adults with opioid use disorder presented with high HIV and HCV risk. At baseline, deficits in HIV and HCV knowledge were observed. A mobile health education intervention significantly improved HIV and HCV knowledge. Gains in HIV and HCV knowledge persisted 3 months following intervention. Abstract: Aims: There is a critical need to reduce infectious disease transmission among individuals with opioid use disorder (OUD). Here we examine the ability of a novel, automated educational intervention, delivered via iPad in a single visit, to improve human immunodeficiency virus (HIV) and Hepatitis C (HCV) knowledge among adults with OUD. Methods: Participants were 25 adults enrolled in a 12-week trial evaluating the efficacy of an Interim Buprenorphine Treatment for reducing illicit opioid use and other risk behaviors during delays to opioid treatment. Participants completed baseline HIV and HCV knowledge assessments with corrective feedback. They then completed an interactive HIV flipbook and HCV video followed by a second administration of the knowledge assessments. The knowledge assessments were repeated at post-intake Weeks 4 and 12. Results: At baseline, participants answered 69% and 65% of items correctly on the HIV and HCV assessments, respectively. The educational intervention was associated with significant increases in knowledge (86% and 86% correct on the HIV and HCV assessments, respectively; p's <.001). These improvements persisted throughout the study, with scores at Week 4 and 12 significantly greater than baseline ( p's <.001). Conclusion: This HIV+Hepatitis Education intervention was associated with significant and sustained improvements in knowledge of HIV + HCV transmission and risk behaviors in this vulnerable group of individuals with OUD. Given the continuing opioid epidemic, efforts are urgently needed to reduce HIV and HCV contraction and transmission among individuals with OUD. Mobile health educational interventions may offer a time- and cost-effective approach for addressing these risks.